2012
DOI: 10.1128/aem.00455-12
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Mutation in the Promoter Region of the Silent cel Cluster Accounts for the Appearance of Lactose-Utilizing Lactococcus lactis MG1363

Abstract: The Lactococcus lactis laboratory strain MG1363 has been described to be unable to utilize lactose. However, in a rich medium supplemented with lactose as the sole carbon source, it starts to grow after prolonged incubation periods. Transcriptome analyses showed that L. lactis MG1363 Lac ؉ cells expressed celB, encoding a putative cellobiose-specific phosphotransferase system (PTS) IIC component, which is normally silent in MG1363 Lac ؊ cells. Nucleotide sequence analysis of the cel cluster of a Lac ؉ isolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…Indeed, the Pcel promoter region contains two binding sites (cre sites) for the CCR transcriptional regulator CcpA (SI Appendix, Fig. S5) (3). We deleted the ccpA gene from the chromosome of L. lactis M1gfp to examine whether population heterogeneity also occurs in the absence of CCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the Pcel promoter region contains two binding sites (cre sites) for the CCR transcriptional regulator CcpA (SI Appendix, Fig. S5) (3). We deleted the ccpA gene from the chromosome of L. lactis M1gfp to examine whether population heterogeneity also occurs in the absence of CCR.…”
Section: Resultsmentioning
confidence: 99%
“…L. lactis M1 is a derivative of L. lactis MG1363, which grows well on cellobiose because of the activation of the Pcel promoter of the cellobiose uptake system IIC component CelB. An active cellobiose/lactose phosphotransferase system (PTS Cel/Lac ) consists of proteins PtcAB and CelB (3). A diauxic shift is seen when L. lactis M1 is propagated in a medium supplemented with both glucose (0.1%) and cellobiose (1%) (G-C medium; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with earlier findings on sulphur-source shifts with yeast [48][49][50] . Earlier studies on different nutrient shifts have reported the existence of a subpopulation of cells that does not respond at all 2,3,5,6 or the occurrence of very dispersed response times 4,7,8 across a range of microbial species. In these cases, stochasticity in the cell population is large, mostly due to stochasticity in response times, leading either to a bimodal or very broad distribution of cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…In both these cases, the lag phases of individual cells vary greatly. The fact that many different adaptation mechanisms can occur may explain the great variation in lag phase durations that have been experimentally observed, which range from minutes to days [2][3][4]7,8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation